Networks and RegionalCompetitiveness: Towards a Transaction Cost Approach of Small-Scale Cooperation (2005)
A preoccupation with competition often dominates the study of governance.  A focus on competition often unnecessarily precludes the possibility that regional institutions can suspend competition in certain areas and facilitate cooperation among potential rivals, thereby potentially contributing to their mutual success.  In many ways, companies cooperating through these types of networks have a greater degree of flexibility than firms which are forced to rely solely on hierarchies or markets for solutions to their problems.  In order to fully understand how such networks work, this article first parses out differences in definitions of networks in order to understand how the type of network mentioned above actually differs from other uses of this term.  Then it develops a theory of governance that goes beyond hierarchies and markets by demonstrating how this type of network can lead to reductions in transaction costs.  This claim is illustrated on hand rom examples of alternative forms of organization in Germany and Italy.